Hubungan Kecemasan Akademik dengan Motivasi Belajar Siswa SMAN 2 Padang - Ayu, Weri; Syahniar, Syahniar (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Motivation to learn is encouragement from within (intrinsic) and from outside (extrinsic) individuals or students to make changes in behavior and to achieve certain goals. Without motivation in learning, learning activities will be difficult to succeed. Learning motivation is influenced by various factors, one of which is psychological factors, namely anxiety. This study aims to: (1) describe student learning motivation, (2) describe students' academic anxiety, and (3) test the significance of the relationship between academic anxiety and student motivation. This study uses quantitative research with descriptive correlational types. The population of this study were 978 students of SMAN 2 Padang who were enrolled in the July-December 2018 semester and a sample of 93 students were selected by Stratified Random Sampling. The instruments used were learning motivation questionnaire with reliability 0.703 and academic anxiety questionnaire with reliability of 0.732. Data were analyzed by descriptive statistical techniques and Pearson Product Moment techniques with the help of SPSS for Windows 20. The research findings showed that: (1) students 'learning motivation was in the medium category with a percentage of 60%, (2) students' academic anxiety was in the medium category with a percentage of 70%, (3) and there is a significant negative relationship between academic anxiety and student motivation with a correlation coefficient of -0.269 and a significance level of 0.009.